The Relationship of Curiosity, Confidence, and Kinesthetic Learning Styles with Interest in Science Learning - Gitatenia, I Dewa Ayu Indah; Lasmawan , I Wayan (Universitas Pendidikan Ganesha, 2022)
The student’s curiosity, self-confidence, and interest in learning science are still low. This situation is also supported by the teacher's way of teaching, which is less attractive so that students feel that science lessons are so boring. This study analyzes the relationship between curiosity, self-confidence, and kinesthetic learning styles interested in learning science. The type of research conducted is the type of ex-post research. This population is 326 students. Determination of the sample in this study using a random sampling technique with the required number of samples, as many as 167 students. The method used in this research is the non-test method. The instrument used is a questionnaire. The data analysis technique used is inferential statistical analysis. This research shows that the significance of curiosity is 0.000 < 0.05, so curiosity has a significant positive relationship with interest in learning science. The significance of self-confidence is 0.024 <0.05, so self-confidence has a significant positive relationship with interest in learning science. The significance of the kinesthetic learning style (x3) is 0.047 < 0.05, so the kinesthetic learning style is significantly positively related to the interest in learning science. It was concluded that curiosity, self-confidence, and kinesthetic learning styles had a significant positive relationship with interest in learning science.